Integrasi Latihan Plyometric dan Analisis Video AI untuk Meningkatkan Efektivitas Jump Shot dalam Basket - Syobri, Nazalus; Indra Kusuma, Angga; Pratama, Raditya; Muhammad; Harwanto (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
ABSTRACT Technological advancements in sports have created new opportunities to enhance training effectiveness, particularly in developing jump shot skills in basketball. This study aims to analyze the impact of integrating plyometric training with AI-based video analysis on improving shot accuracy and jump height. The research employs an experimental method with a pretest-posttest control group design. The population consists of university-level basketball athletes, with a sample of 30 players divided into an experimental group and a control group. The experimental group underwent plyometric training combined with AI video feedback, while the control group performed conventional plyometric exercises. The results indicate that the experimental group experienced a significant improvement in shooting accuracy and jump height compared to the control group (p < 0.05). These findings suggest that AI-based video analysis provides more objective and effective feedback for enhancing athlete performance. Therefore, coaches are encouraged to adopt this technology in training programs to optimize player skill development.